Integrating ChatGPT to Enhance Students’ Morphological Awareness of Technical Tourism Terms - Vera Kristiana; Ayu Melati Ningsih (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The rapid advancement of Artificial Intelligence (AI) has opened new pathways for English for Specific Purposes (ESP) pedagogy, particularly in the acquisition of technical vocabulary. This study aims to investigate the integration of ChatGPT in enhancing students’ morphological awareness of tourism-related technical terms. Employing a quasi-experimental design, the study involved two groups of tourism students: an experimental group that used ChatGPT-assisted learning and a control group that followed conventional dictionary-based methods. Data were collected through pre-tests and post-tests focusing on morphological decomposition and word formation tasks, complemented by semi-structured interviews. The findings reveal that the experimental group significantly outperformed the control group in identifying derivational affixes and understanding compound words specific to the tourism industry. ChatGPT provided personalized, real-time linguistic explanations, thereby facilitating deeper cognitive processing of complex terminology. The study concludes that AI integration not only enhances morphological competence but also promotes learner autonomy. These results suggest that ESP practitioners should strategically incorporate AI tools to bridge the gap between theoretical linguistics and professional communication in the field of tourism.